Development of an AHP-Based Multi-criteria Decision Model for Prioritizing Road-Related Infrastructure in Cameroon: Case Studies of Bogo-Guirvidig and Bingambo-Grandzambi Projects - Fabrice Fortune Mvondo; Jean François Wounba; Georges Elambo Nkeng (Universitas Negeri Surabaya or The State University of Surabaya, 2026)
Road development projects in Cameroon often fail to address multidimensional poverty and human exclusion, particularly in regions with contrasting socio-economic conditions like the conflict- affected Far North and resource-rich South. This study proposes a systematic approach to prioritize infrastructure investments that reduce exclusion by integrating the Analytic Hierarchic Process (AHP) with multidimensional exclusion indices. The work extends existing AHP applications in Sub-Saharan Africa by incorporating exclusion metrics, offering a replicable framework for inclusive infrastructure planning in developing contexts. The AHP method was applied using expert judgments from local authorities and community representatives to evaluate criteria linked to human exclusion. Case studies from Bogo-Guirvidig (Far North) and Bingambo-Grandzambi (South) provided contrasting regional insights. Sanitation infrastructure, educational infrastructure, rural road development, and water access emerged as top priorities for reducing exclusion. The model demonstrates how targeted investments alongside road projects can significantly improve equity. The study provides actionable insights for policymakers to allocate resources effectively, emphasizing the need for context-sensitive infrastructure planning to combat multidimensional poverty.